2007
DOI: 10.1111/j.1365-3148.2007.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood donor deferral rate and characteristics of the Turkish population

Abstract: Whole blood (WB) donors are deferred for several reasons, either permanently or temporarily. In this retrospective study, we quantified the rate of and reasons for donor deferral among Turkish donors. Computer records of the last 5 years were analysed to quantify the deferral rate and reasons. Deferrals were categorized as temporary short-term (1-56 days), long-term (57-365 days) and multiple years or permanent (more than 365 days). Deferred donors were also analysed according to gender, age and education leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
47
7
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 14 publications
15
47
7
3
Order By: Relevance
“…A similar rate have been found in study by Rehman et al with temporary (63.73%) and permanent (36.3%) [9]. Whereas Arslan et al have reported a rate of 10% and 90% among permanent and temporary deferrals respectively [10]. The Leading cause of permanent deferral was hypertension 30.3%.…”
Section: Discussionsupporting
confidence: 82%
“…A similar rate have been found in study by Rehman et al with temporary (63.73%) and permanent (36.3%) [9]. Whereas Arslan et al have reported a rate of 10% and 90% among permanent and temporary deferrals respectively [10]. The Leading cause of permanent deferral was hypertension 30.3%.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings (36.3%) were much higher than Custer et al [7] who reported a permanent deferral rate of 10.6% and Arslan [9] who reported a rate of 10%. This high frequency was due to the inclusion of transfusion transmissible infection in our study especially Hepatitis B infection (HBV) which was not studied thoroughly in the above mentioned publications.…”
Section: Resultscontrasting
confidence: 55%
“…In a European study conducted by Lawson-Ayayi and Salmi [8], 10.8% of donors were deferred. Arslan [9] reported a donor deferral rate of 14.6% in Turkish donors. Lim et al [10] reported a deferral rate of 14.4% in Singapore (Asia) and Bahadur et al [4] reported 9% in Delhi (India).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the donors i.e., 91.6% in our study were males and female donors were only 8.4%, Chaudary et al [3] and Arslan [7] found similar differences in male and female donation trends which may be due to hesitation in society towards female donation. There is still huge difference between number of males and females turning up for donation.…”
Section: Discussionmentioning
confidence: 55%